Association of the oral microbiota dynamics with complications and outcomes in allogeneic hematopoietic stem cell transplant - Heidrich, Vitor (2023)
Allogeneic hematopoietic stem cell transplant (allo-HSCT) is a potentially curative therapy for several hematological disorders. Before stem cell infusion, recipients undergo a conditioning regimen with chemo/radiotherapy and immunosuppressants, requiring the use of antibiotics to treat and prevent infections. This regimen promotes drastic alterations in the recipients gut microbiota, which have been associated with allo-HSCT complications and poor outcomes. Similar studies on the oral microbiota of allo-HSCT recipients are scarce and disregard the existence of distinct microbiotas within the oral cavity. Here, we used 16S rRNA gene sequencing to characterize the microbiota dynamics at three oral sites (gingival crevicular fluid, oral mucosa, and supragingival biofilm) during and after allo-HSCT. We used this data to associate the oral microbiota with an allo-HSCT toxicity (oral mucositis), allo-HSCT complications (graft-versus-host disease and bacterial infections), and allo-HSCT outcomes (progression-free survival, overall survival, and risk of underlying disease relapse, non-relapse death, and transplant-related death). In the first chapter, we analyzed the influence of the oral mucosa microbiota in the oral mucositis clinical course. We found taxa associated with higher oral mucositis grade (Porphyromonas), and lower time to oral mucositis healing (Lactobacillus). In the second chapter, we evaluated the association between supragingival biofilm microbiota and graft-versus-host disease risk. We identified taxa at preconditioning associated with higher (Streptococcus and Corynebacterium) and lower (Veillonella) risk of acute graft-versus-host disease, and observed that Enterococcus faecalis blooms during allo-HSCT were present in all patients developing this condition. Inthe third chapter, we explored the association between oral mucosa microbiota and allo-HSCT outcomes. We noticed that preconditioning oral microbiota dysbiosis (low diversity or dominance by a single genus) was associated with poorer outcomes, such as shortened overall survival. Finally, in the fourth chapter, we analyzed samples from all oral sites. We observed that the microbiota of all three oral sites was damaged during allo-HSCT, which translated into a loss of differences between microbiota compositions of each site. Despite the loss of diversity and blooms of pathogenic genera observed during allo-HSCT (which preceded respiratory complications caused by the blooming bacteria in some cases), oral microbiotas were able to return to their initial state after engraftment, even though recovery levels varied between patients. After stratifying patients based on their ability to recover their preconditioning microbiota, we found that patients able to recover their oral mucosa microbiota composition showed earlier reconstitution of normal leukocyte counts in the bloodstream. Most notably, oral mucosa microbiota composition recovery was not associated with antibiotic usage and was an independent biomarker of better allo-HSCT outcomes. In summary, we identified clear patterns of dysbiosis in the oral microbiota during allo-HSCT. The oral microbiota of allo-HSCT recipients was associated with oral mucositis clinical course, allo-HSCT complications and allo-HSCT outcomes, highlighting the clinical value of tracking oral microbiota changes during allo-HSCT.